**Ln E X**

### LN (ex) to express evenly / or logarithmic time difference? How to express?

Usually when you are in good health

In (a * b), you can rewrite it:

ln (a * b) = ln (a) + ln (b)

So in this case ln (e * x) = In (e) + ln (x)

Note that ln (e) = 1, so you can simplify this way.

(e * x) = 1 + ln (x)

Another law of logarithm that helps to remember is

ln (a / b) = ln (a) ln (b)

Help for example! :)

For example, suppose your question is based on e-natural logarithm (e = 2.718 ...)

ln (e x) = x * ln (e) = x because ln is the inverse of e. This

ln (e * x) = ln (e) + ln (x) = 1 + ln (x)

General Logarithm Principle (LD for any basis, not just LN):

ln (a * b) = ln (a) + ln (b)

ln (a / b) = ln (a) ln (b)

ln (a b) = b * ln (a)

ln (e) = 1

What Ben said ... but ln (e) = 1

I don't know if your teacher wants you to simplify or not

ln (for example) = ln (e) + ln (x)

The nature of the natural stem